Modelling experiments of the variations of the calving front position of Hansbreen, Svalbard - Navarro Valero, Francisco José; Otero García, Jaime; Lapazaran Izargain, Javier Jesús; Robinson, Alexander (E.T.S.I. Telecomunicación (UPM), 2013)
Hansbreen is a tidewater glacier in Svalbard, with grounded tongue, about 16 km in length and ca. 2.5 km in width at its tongue. The calving front position has shown, over the recent decades, a general retreating trend, often rather smooth but with some occasional abrupt changes. We apply a full-Stokes model of glacier dynamics, incorporating a crevasse-depth calving model, with the aim of reproducing the glacier front positions observed since 1936 and analyzing the sensitivity of the model to environmental parameters.